Physiological Responses to Oxidative Stress of Different Chlorella vulgaris Isolates - Dilyana Doneva; Juliana Ivanova; Lyudmila Kabaivanova (International Journal Bioautomation, 2019)
Oxidizing agents, notably hydrogen peroxide (H2O2), are increasingly used in a number of applications. Their manner of action on algae was investigated in this work. Different concentrations of H2O2 and silver ions were applied to the algal cultures to follow the effect of their action in antarctic and mesophilic isolates of the green alga Chlorella vulgaris. Oxidative stress-induced physiological responses manifested by changes in the photosynthetic apparatus and antioxidant enzymes were estimated. The algae from the antarctic region appeared to be less resistant to oxidative stress than their mesophilic counterparts, concerning growth after treatment with higher concentrations of the reagent. The increased concentration (0.05%) lead to raise of activity and isoenzyme number of catalase (CAT) in both C. vulgaris strains. The isoenzyme activity of peroxidase (POX) decreased and disappeared in the antarctic isolate. At the same time the highest concentration (0.08%) provoked restoration of POX activity in the mesophylic one. Decrease in superoxide dismutase (SOD) activity was registered and this effect was more intensive in the moderate and fast mobile isoenzymes. Isoenzyme profile at 0.08% reagent concentration for the mesophylic isolate was similar with this at 0.05% for the antarctic isolate and a fourth isoenzyme appeared.